Influence of aging on bond strength of artificial teeth to denture base acrylic resins - Etiene Faria Aguiar; Rafaella Tonani; Fabiana de Goes Paiola; Michelle Alexandra Chinelatti; Carolina Noronha Ferraz de Arruda; Julio César Souza da Matta; Fernanda de Carvalho Panzeri Pires- (Universidade Estadual de Campinas, 2018)
Aim: The aim of this study was to evaluate the bond strength of artificial teeth to different types of denture base resins when submitted to thermomechanical cycling (TMC). Methods: Sixty artificial mandibular first molars (Trilux, Vipi) were randomly divided into 3 groups according to denture base acrylic resins (Vipi Wave, Vipi Cril, and Vipi Cril Plus, Vipi). The teeth were fixed onto self-polymerizing acrylic resin bars (0.5 cm2 cross-section x 2 cm height), and the set was included in a metal flask using dental stone/silicone. After the dental stone was set, the bar was removed, and the denture base resin was packed and processed according to the group studied (Vipi Wave: 180 W/20 minutes + 540W/5 minutes; Vipi Cril and Vipi Cril Plus: Water bath at 74ºC for 9h). After polymerization, the samples were divided into 2 groups (n=10), according to the TMC treatment received (simulation of 5 years of mastication or not). The samples were submitted to tensile bond strength test (1 mm/min), and the data (MPa) were statistically analyzed (2-way ANOVA, Bonferroni, α=0.05). The fracture interfaces were evaluated using a stereomicroscope (50x). Results: The bond strength results showed no statistically significant difference (p>0.05) between the resins studied. TMC was significant (p<0.05), demonstrating lower values for the bond strength of artificial teeth to Vipi Cril Plus. The predominant fracture type was cohesive in resin. Conclusions: It was concluded that there is no difference in bond strength between artificial teeth and the resins used for denture base. However, TMC decreases the bond strength values of artificial teeth and crosslink thermo-polymerizable acrylic resin.